1989
DOI: 10.1037/0735-7044.103.3.561
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of function after brain damage: Facilitation by the calcium entry blocker nimodipine.

Abstract: Large neocortical injuries can interfere with the initial performance of many previously learned behaviors. This dysfunction, however, may not be attributable to the loss of the memories of learned behaviors but to a failure to access memories that are spared. The results of this experiment support this hypothesis by demonstrating that the calcium entry blocker nimodipine, which prevents trauma-induced retrograde amnesia in a 1-trial passive learning situation, will also facilitate the recovery of pre-operativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
1

Year Published

1991
1991
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(13 citation statements)
references
References 16 publications
(31 reference statements)
0
12
1
Order By: Relevance
“…Nimodipine administration has also been reported to reverse trauma-induced retrograde amnesia following bilateral aspiration of the visual neocortex in rats (LeVere et al, 1989) and to dilate pial arterioles and induce angiogenesis in rat cortex (Yuan et al, 1990). Dihydropyridine calcium channel blockers have recently been evaluated in a series of clinical trials in TBI.…”
Section: Calcium Channel Blockersmentioning
confidence: 98%
“…Nimodipine administration has also been reported to reverse trauma-induced retrograde amnesia following bilateral aspiration of the visual neocortex in rats (LeVere et al, 1989) and to dilate pial arterioles and induce angiogenesis in rat cortex (Yuan et al, 1990). Dihydropyridine calcium channel blockers have recently been evaluated in a series of clinical trials in TBI.…”
Section: Calcium Channel Blockersmentioning
confidence: 98%
“…Similar results were obtained when the hypoxic insult was replaced with a hypoglycemic one (Schurr et al, 1990;1991a). Other recent studies have shown partial success in protecting brain tissue in vivo against hypoxicischemic or other cell injury by calcium antagonists such as (S)-emopamil (Ginsberg et al, 1991) and nimodipine, nicardipine, or isradipine (Bunnell et al, 1987;Grotta et al, 1988;Hadani et al, 1988;LeVere et al, 1989;Sauter et al, 1988;Sauter and Rudin, 1990;Greenberg et al, 1991; see also a review by Horowitz and Powell, 1989). In an immunocytochemical study, Leranth and Ribak (1991) showed that calcium-binding proteins are concentrated in the hippocampal CA2 region, which may explain this region's high resistance to epileptic damage and other damage-causing insults such as hypoxia and ischemia.…”
Section: Calcium and Cerebral Hypoxic-ischemic Damagementioning
confidence: 55%
“…Clinical trials in TBI suggest that some benefit is seen in the subgroup of patients that are younger and those with traumatic subarachnoid hemorrhage (tSAH) [180]. In animal studies these agents have been shown to improve regional CBF, decrease cerebral edema, prevent injury related amnesia, improve recovery of passive learning and lessen motor deficits [181][182][183]. Unfortunately, a recent European multicenter clinical trial found no significant benefit in the use of nimodipine in TBI patients, but there was a trend towards benefit in the subgroup with tSAH [184].…”
Section: Receptor Channelsmentioning
confidence: 99%